A COVID-19 patient’s experience: Engagement in disease management, interactions with care teams and implications on health policies and managerial practices - Lihua Dishman (The Beryl Institute, 2020)
This narrative inquiry aimed to explore a COVID-19 patient’s lived experience from contracting the disease to recovery and understand the implications of this unique patient experience on health policies and managerial practices. The personal narrative approach was used to chronicle the patient’s weekly journey in disease management. Best practices emerged from her and her family members’ engagement in managing COVID-19, and interactions with her primary care provider and COVID-19 Response Team. Her COVID-19 patient experience also provided a basis for implications on public health and healthcare policies and managerial practices. Three key dimensions were perceived to have positively impacted the COVID-19 patient’s experience and health outcomes: information seeking, communication, and self-awareness. Physical, mental and emotional support from family members were also perceived to have a positive impact on the patient’s experience and outcomes. Three key dimensions were perceived to have negatively impacted the COVID-19 patient’s experience and health outcomes: federal government’s lack of coordination in crisis management, CDC’s slow actions in disease control and prevention and primary care provider’s absence in care continuity. Patients must take active ownership and engage consistently in their disease management, which could help improve their own experiences and overall health outcomes. Proactive engagement in care and in making treatment decisions may improve disease outcomes even when coordinated responses to health crises were lacking in the country and care continuity by providers was absent. Interactions with care providers also present opportunities for patients to help providers improve their practices. Patients are integral members of care teams. Experience Framework This article is associated with the Infrastructure & Governance lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Infrastructure%20%26%20Governance%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.